Chemically Active Elements of Reservoir Quartz Cement Trace Hydrocarbon Migration in the Mahu Sag, Junggar Basin, NW China. (8th April 2021) - Huang, Linjun; Liu, Yin; Bian, Baoli; Ma, Yongping; Liu, Hailei; Guo, Juanjuan; Cao, Jian
Abstract : Element exchange and enrichment during fluid-rock interactions are common, providing potentially novel proxies to trace hydrocarbon migration in addition to the traditional organic geochemistry tracers. However, the processes, mechanisms, and geological and geochemical fingerprints of these interactions are complex, hampering the applications of hydrocarbon migration tracers. To investigate such interactions, we conducted a petrological, mineralogical, and in situ and bulk geochemical study of authigenic quartz and whole-rock samples from the Mahu Sag, northwestern Junggar Basin, northwest China. We found that dissolution, clay and chlorite formation, and overgrowth occurred on quartz grains in hydrocarbon fluid migration pathways, suggestive of strong fluid-rock interactions. In situ quantitative elemental analysis of quartz grains revealed elemental enrichment (e.g., Mn, Fe, Al, Sr, and W) in quartz overgrowth rims compared with their cores, indicating that migration of hydrocarbon-bearing fluids in reservoirs may promote elemental exchange between fluids and minerals. Whole-rock geochemical analysis showed that decreasing contents of some elements may reflect the direction of hydrocarbon-bearing fluid migration and can be monitored with three geochemical proxies, which are the MnO contents and MnO/Zr and Y/Ho ratios. Our data provide new constraints on fluid-rock interactions in petroleum reservoirs and have implications for using inorganic geochemical methods to trace hydrocarbon migration.